SPACE AND TEMPORARY VARIABILITY OF THE INDEX VEGETATION APPLIED TO IMAGES OBTAINED BY A REMOTELY PILOTED AIRCRAF - Gonçalves, L. M.; Barbosa, B. D. S.; Ferraz, G. A. e S.; Maciel, D. T.; Santos, H. F. D. (Revista Brasileira de Engenharia de Biossistemas, 2017)
High resolution images obtained with the aid of Remotely Piloted Aircraft (RPA), when properly treated, can be a useful tool for the practice of precision agriculture, monitoring the growth and development of the crop on a suitable temporal and spatial scale. In this sense, this work aimed to use images obtained with a digital camera coupled to a RPA to analyze the spatial and temporal variability of the MPRI vegetation (IV) index applied in a São Carlos grass production area. The images were collected during the period from December 2016 to March 2017, using an autonomous flight quadricopter with RGB camera and flight height of 50 m. The image processing and the MPRI IV application were performed using a free geoprocessing software. Average MPRI values ​​were generated for all scenes. It was possible to detect the variability of MPRI in all scenes. A determination index (R²) of 0.89 was found due to the correlation between MPRI values ​​and time after grass cutting. It can be inferred from the results obtained that the use of this technology has great potential for monitoring and evaluation of the areas cultivated with grass.